SATIRE AND COMEDY AS TOOLS FOR CRITIQUE IN THE COMEDY “PYGMALION” BY B. SHOW - Jononova Gulbahor Farxod qizi (Bright Mind Publishing, 2025)
This article explores the social issues reflected in Bernard Shaw’s Pygmalion, a witty yet sharp social commentary wrapped in the form of a comedy. Through its portrayal of class mobility, gender roles, education, and linguistic discrimination, Pygmalion challenges Edwardian Britain's rigid societal structure. Shaw combines irony, satire, and the transformation myth to highlight injustices in class-based society and to advocate for progressive change through education and self-awareness.
Keywords: Playwright, comedy, social critic, myth, speech and manners, accent, women’s emancipation.